An Econometric Study of The Impact of Technology on Moving Countries to higher income paths During the period (1990-2018) - Tahar Chermat; Ahmed Hadroug; Ali Djouadi (Dirassat Journal Economic Issue, 2022)
The objective of this research is to analyse the impact of technology on the transition of countries from low and middle income paths to higher income paths, and the exit from the middle and low income trap and bring about the economic convergence. To achieve the objective of this study, a sample of 105 economically different countries was chosen, then building a logistic regression model during the period (1990-2018). The empirical results of the study indicates that is the existence of a significant effect of the technology impact on increasing the Probability of low and middle income countries moving to higher income paths and creating an economic convergence between them.